THE EFFECTIVENESS OF VSTEP.3-5 SPEAKING RATER TRAINING - Ngoc Quynh, Nguyen Thi; Quynh Yen, Nguyen Thi; Thu Hien, Tran Thi; Phuong Thao, Nguyen Thi; Sao, Bui Thien; Chi, Nguyen Thi; Hoa, Nguyen Quynh (VNU Journal of Foreign Studies; Vol 36 No 4DO - 10.25073/2525-2445/vnufs.4577, 2020)
Playing a vital role in assuring reliability of language performance assessment, rater training has been a topic of interest in research on large-scale testing. Similarly, in the context of VSTEP, the effectiveness of the rater training program has been of great concern. Thus, this research was conducted to investigate the impact of the VSTEP speaking rating scale training session in the rater training program provided by University of Languages and International Studies - Vietnam National University, Hanoi. Data were collected from 37 rater trainees of the program. Their ratings before and after the training session on the VSTEP.3-5 speaking rating scales were then compared. Particularly, dimensions of score reliability, criterion difficulty, rater severity, rater fit, rater bias, and score band separation were analyzed. Positive results were detected when the post-training ratings were shown to be more reliable, consistent, and distinguishable. Improvements were more noticeable for the score band separation and slighter in other aspects. Meaningful implications in terms of both future practices of rater training and rater training research methodology could be drawn from the study.